THE EFFECT OF RED ONION FILTRATE CONCENTRATION TOWARDS VEGETABLE CANE CUTTING GROWTH - JASANI JASANI; DINI ANGGOROWATI; INPURWANTO INPURWANTO (Jurnal Sains Pertanian Equator, 2018)
THE EFFECT OF RED ONION FILTRATE CONCENTRATION TOWARDSVEGETABLE CANE CUTTING GROWTHJasani1, Dini Anggorowati2, Inpurwanto31Agriculture; Faculty University of Tanjungpura2Agriculture; Faculty University of Tanjungpura3Agriculture; Faculty University of Tanjungpurae-mail: *jasaninaang96@gmail.comABSTRACTThe objective of this research was aimed to find the best red onion filtrate concentration for vegetable cane cuttings growth. This research was conducted in 25th November 2017 until 17th February 2018 at experimental garden of Agriculture Faculty Tanjungpura University Pontianak. This research used Completely Randomized Design (CRD), consist of 5 treatments with 5 replications in which every replication contain 5 samples. The treatments in this research were p0 = without red onion filtrate, p1 = with red onion filtrate concentration 25%, p2 = with red onion filtrate concentration 50%, p3 = with red onion filtrate concentration 75%, and p4 = with red onion filtrate concentration 100%. The variables observed were living stem cutting percentage (%), plants height (cm), the number of leaves per plants (sheets), the number of buds (buds), roots volume (cm3), roots dry weight (gram), and buds dry weight (gram). The result of this research showed that the treatment with red onion filtrate concentrate 75% gave the best effect for roots volume, roots dry weight, and buds dry weight of vegetable cane cuttings growth.Keywords: Red Onion Filtrate, vegetable cane cuttings